The anthropology of modern human teeth : dental morphology and its variation in recent human populations - Scott, George Richard, 1946-; Turner, Christy G. (Cambridge : Cambridge University Press, 2015)
All humans share certain components of tooth structure, but show variation in size and morphology around this shared pattern which is studied by dental anthropologists. This book presents the first worldwide synthesis of the global variation in tooth structure in recent populations. It: * describes the methods and assumptions used by dental anthropologists * discusses the genetic basis of nonmetric dental traits * portrays the geographic variation of tooth crown and root traits * analyzes dental variation on a global scale paralleling major genetic and craniometric analyses The book illustrates more than 30 tooth crown and root traits and reviews their biological and genetic underpinnings. This analysis links extinct and extant populations and so serves as a useful tool for elucidating population relationships and histories.
1. Dental anthropology and morphology -- 2. Description and classification of permanent crown and root traits -- 3. Biological considerations: ontogeny, asymmetry, sex dimorphism, and intertrait association -- 4. Genetics of morphological trait expression -- 5. Geographic variation in tooth crown and root morphology -- 6. Establishing method and theory for using tooth morphology in reconstructions of late Pleistocene and Holocene human population history --7. Tooth morphology and population history -- App. A. Information base for global descriptions and analysis -- App. A1. Samples used in regional characterizations and map -- App. A2. Regional crown and root trait frequencies (with sample sizes)
Keywords: zuby; antropologie; teeth; anthropology; e-knihy online; e-books online